ANALYSIS OF CUPREDOXIN AND COEXPRESSED PROTEINS OF PSEUDOMONAS AERUGINOSA LESB58 USING BIOINFORMATICS TOOLS - Khan, Muhammad Tahir; Rashid, Hamid (European Scientific Journal, ESJ, 2014)
Objectives: To identify the bioinformatics tools that can be used as the easiest source to analyze the properties of proteins. This activity will also enable the researchers to easily apply and predict drug target sites and other biotechnological researches against microbial infections. Methodolgy: Cupredoxin and the co-expressed partners’ retrieved from string database are mainly responsible for electron transfer and other important functions. The current analysis was conducted to investigate the amino acids composition, structure, hydropathecity, phylogenetic analysis, aliphatic index molecular weight and some other properties of cupredoxin and its functional partners of pseudomonas aeruginosa LESB58 using bioinformatics tools. Results: The analysis showed that some of the functional partners of cupredoxin are unstable. These protein located in periplasmic space and cytoplasm. Leucine is the most abundant amino acid followed by alanine. Majority of amino acids possess negative charge. Phylogenitically all these proteins have common ancestor. Conclusion: Bioinformatics tools can easily be applied to study the characteristics and comparison of different proteins.